2008
DOI: 10.4049/jimmunol.181.1.746
|View full text |Cite
|
Sign up to set email alerts
|

The Anergic State in Sarcoidosis Is Associated with Diminished Dendritic Cell Function

Abstract: Sarcoidosis is a chronic inflammatory disease of unknown cause, characterized by granuloma formation similar to tuberculosis, but without clear evidence of a microbial infection. Because sarcoidosis is linked with clinical anergy and other evidence of diminished cellular immunity, we hypothesized that decreased skin delayed-type hypersensitivity (DTH) responses to recall Ags in affected individuals would be associated with decreased function of their blood dendritic cells (DCs). Our study involved ex vivo isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 53 publications
(48 reference statements)
6
67
2
Order By: Relevance
“…In sarcoidosis BAL fluid (34) and in blood (55), pDCs appear in similar frequency and absolute numbers as in normals. Stimulation of sarcoidosis and normal blood pDCs with TLR9 ligand CpG-A showed no difference in IFN-a protein expression.…”
Section: Plasmacytoid Dcs Do Not Play a Large Role In Sarcoidosis Patmentioning
confidence: 89%
See 1 more Smart Citation
“…In sarcoidosis BAL fluid (34) and in blood (55), pDCs appear in similar frequency and absolute numbers as in normals. Stimulation of sarcoidosis and normal blood pDCs with TLR9 ligand CpG-A showed no difference in IFN-a protein expression.…”
Section: Plasmacytoid Dcs Do Not Play a Large Role In Sarcoidosis Patmentioning
confidence: 89%
“…The immunostimulatory capacity of sarcoidosis BAL fluid is inhibited with anti-CD86, suggesting that their ability to induce T cell proliferation is dependent on CD86 co-stimulatory molecule (42). Myeloid DCs from sarcoidosis peripheral blood are also less immunostimulatory than normal blood DCs, and immunostimulatory capacity is directly correlated with ability to mount a delayed-type hyper- sensitivity (DTH) response (55). Decreased DC function is a potential mechanism for sarcoidosis-induced anergy, and may suggest that reduced cellular immunity at the end organs is responsible for disease perpetuation rather than resolution.…”
Section: Sarcoidosis Lung and Peripheral Blood Dcs Are Less Immunostimentioning
confidence: 99%
“…In addition, it has recently been shown that OS9 interacts with the cytoplasmic tail of the dendritic cell-specific transmembrane protein during toll-like receptor-induced maturation of dendritic cells suggesting a role for OS9 in myeloid differentiation and cell fusion [52]. Dendritic cells have been discussed as important mediators of sarcoidosis immunology [53] and have been widely investigated with regards to various aspects of sarcoidosis [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Mathew et al found that mDCs from sarcoidosis subjects had, ex vivo, a significantly decreased ability to stimulate T cells, compared to mDCs from healthy controls, despite normal cell count and up-regulated co-stimulatory and maturation markers, resulting, in vivo, in a reduced skin delayedtype hypersensitivity (DTH) to recall antigens in affected individuals. Nevertheless, the function of T cells in patients with sarcoidosis remained relatively preserved (12), In sarcoidosis, mDCs dysfunction may contribute to reduce the ability to eliminate antigenic stimuli, favoring the typical chronic inflammatory state, and may contribute to reducing the tumor immune surveillance. An altered maturation of mDC has indeed been found in various tumors (e.g.…”
Section: Dendritic Cells (Idcs) Take Antigens and Process Them Into mentioning
confidence: 99%
“…Furthermore, an anergic state (poor response to antigens in vitro and in vivo) can occur. These events, also known as the "immune paradox" of sarcoidosis, remain unexplained and have been attributed to a diminished myeloid dendritic cell (mDC) function and to a disequilibrium between effector and T-regulatory (T-reg) cells, resulting in a diminished cellular immunity (11,12). Myeloid DCs are descendants of blood myeloid hematopoietic …”
Section: Dysregulation Of the T-cell System And The Immune Paradox Ofmentioning
confidence: 99%